Enhanced power factor and thermoelectric performance for n-type Bi2Te2.7Se0.3 based composites incorporated with 3D topological insulator nanoinclusions. (February 2021) - Jabar, Bushra; Qin, Xiaoying; Mansoor, Adil; Ming, Hongwei; Huang, Lulu; Danish, Mazhar Hussain; Zhang, Jian; Li, Di; Zhu, Chen; Xin, Hongxing; Song, Chunjun
Abstract: n-type Bi2 Te2.7 Se0.3 (BTS) alloy is a state-of-the-art room temperature thermoelectric material used for refrigeration commercially. However, wide application is limited by its low performance. Here, we show that incorporation of nano-sized 3D topological insulator (3D-TI) Bi2 Se3 in Bi2 Te2.7 Se0.3 bring about a large electron mobility and increased electrical conductivity owing to the enhanced contribution of topologically protected conducting surface states as well as large Seebeck coefficient due to energy dependent carrier scattering. Besides, the incorporation of 3D-TI nanoinclusions leads to enhanced phonon scattering. As a result, addition of 0.3 vol% of Bi2 Se3 in BTS results in 36% increase in power factor and 16% decrease in total thermal conductivity, leading to a large figure of merit ZTmax = 1.28 (at 375 K) and a large average ZTave = 1.16 (at T = 300–525 K), which are 62% and 59% greater than that of BTS, respectively. Graphical Abstract: Through incorporation of a small amount of (e.g. 0.3 vol%) nano-sized 3D topological insulator Bi2 Se3 in n-type Bi2 Te2.7 Se0.3 36% increase in power factor and 16% decrease in total thermal conductivity are achieved simultaneously, which allow us to obtain a large ZTmax = 1.28 (at 375 K) and a large average ZTave = 1.16 (at T = 300–525 K). ga1 Highlights: Nanocomposite Bi2 Se3 /Bi2 Te2.7 Se0.3 embedded with topological insulator is prepared. Carrier mobility increases due to contribution of surface states of topological insulator. Enhanced thermopower from energy-dependent scattering is realized simultaneously. The achieved ZTave = 1.16 (at T = 300–525 K) has prospect in low-grade heat recovery.